Modelling colour changes during the caramelisation reaction - Quintas, Mafalda A.C. (2007)
Sucrose solutions, with concentrations near or superior to saturation, present high potentialities for the candy and pastry industries. The development of colour in a neutral and highly concentrated sucrose solution (16.32%(w/w) water content) subjected to isothermal heat treatment (in the 100–160 C range) was investigated. Under such conditions, sucrose degrades through caramelisation and 5- hydroxymethylfurfural (HMF) is formed. Colour development was monitored through lightness/darkening (L/L0) and total colour difference (TCDH) changes during reaction course. Kinetic behaviour was mathematically described using modified Gompertz equations. The effect of temperature on the reaction was described by an Arrhenius type dependency. Colour development and sucrose degradation kinetic parameters were compared and similar lag phases were found. However, the same was not observed for reactions rate, indicating that not only sucrose degradation contributes to colour development. To investigate the colour development/HMF content relationship, a fractional conversion and a power law models where successfully proposed to express, respectively, L/L0 and TCDH dependence on HMF content.